Identification of Abrasion-Prone Areas Based on Vertical Electrical Sounding at Geotourism Beach Pasar Bawah South Bengkulu - Nur Husniatin Kamila; Suhendra Suhendra; Halauddin Halauddin; Clora Ulandari; Basdiki Hasugian; M Riski Al Akbar; Hana Raihana; Andre Rahmat Al Ansory (Universitas Andalas, 2025)
This research was conducted to investigate abrasion-prone areas using the Vertical Electrical Sounding (VES) method at Pasar Bawah Manna Beach, South Bengkulu Regency. Data collection using a track length of 200 with the MAE X612-EM geoelectric tool that runs along the abrasion-prone area. Data processing using IP2WIN software and satellite images. This study aims to determine the subsurface of abrasion-prone areas and rock characteristics of abrasion. The results of this study indicate that the research location has seawater ntrusion that seeps into the aquifer with a resistivity value of (0.763 - 8.01 Ωm) and the rock formation of the research area is dominated by alluvium rocks including gravel (130 - 356. 2 Ωm), clay (14.65 Ωm), silt (16.5 -61.41 Ωm), sand (258 - 313 Ωm), sandstone (97.6 Ωm), passive gravel (1496 Ωm), and limestone (2560 Ωm). Based on satellite image data, abrasion-prone is identified from several points in the study area that have significant shoreline changes at sounding point 1 where the point from 2008 to 2023 shows that abrasion has occurred quite significantly over the past 15 years, where at Sounding point 1 abrasion occurs along ± 23 meters / year. The findings of this research are expected to provide knowledge about disaster mitigation in sustainable tourism governance.